Efficient Nutrient Management Practices for Sustainable Rice Production and Soil Health - Vijayakumar, S.; Nithya, N.; Kumar, S. Arun; Jasudasu, G. S.; Gobinath, R.; Basavaraj, K. (Chronicle of Bioresource Management, 2023)
Most of the Indian soils have shown symptoms of fatigue with respect to secondary and micro nutrients due to the sub-optimum application of fertilizers to cereals and taking heavy harvests year after year. Crop productivity is directly influenced by the nutrient availability in the soil and their use efficiency. Considering the low productivity of many agricultural commodities, there is a need to increase fertilizer consumption and also the productivity of agricultural crops. Agro-climatic-region and crop specific fertilizers application should be offered to the farmers to overcome nutrient deficiencies particularly secondary and micronutrients for better crop response and higher productivity. Use of precision farming technologies that consider spatial variability and help conserve natural resources should be promoted. We require a clear-cut and comprehensive long-term fertilizer policies to improve productivity and generate marketable surplus by improving the nutrient use efficiency.